Relevansi Ajaran Al-Qur'an Dan Hadist Dalam Era Modern - Rizadiliyawati, Rizadiliyawati; Agustiar, Agustiar (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The aim of this research is to analyze the relevance of the teachings of the Qur'an and Hadith in the modern era. This type of research is a library study. Data collection with documentation. Data analysis with SLR. The research results Opportunities to strengthen the application of the teachings of the Qur'an and Hadith in the modern era lie in the integration of more innovative and relevant religious education, the use of digital technology for broader and more effective da'wah, as well as collaboration between ulama, academics and society in interpret and apply religious teachings according to the context of the times. By prioritizing an inclusive and adaptive approach, as well as accommodating modern social and cultural dynamics, the teachings of the Qur'an and Hadith can remain relevant and provide solid guidance for Muslims in facing today's challenges and opportunities.